A Candidate Gene Association Study of Bone Mineral Density in an Iranian Population - Dastgheib, Seyed Alireza; Gartland, Alison; Tabei, Seyed Mohammad Bagher; Omrani, Gholamhossein Ranjbar; Teare, Marion Dawn (Frontiers in Endocrinology, 2016)
The genetic epidemiology of variation in bone mineral density (BMD) and osteoporosis is not well studied in Iranian populations and needs more research. We report a candidate gene association study of BMD variation in a healthy cross sectional study of 501 males and females sampled from the IMOS study Shiraz, Iran. We selected to study the association with 21 SNPs located in the 7 candidate genes LRP5, RANK, RANKL, OPG, P2RX7, VDR and ESR1. BMD was measured at the three sites L2-L4, neck of femur and total hip. Association between BMD and each SNP was assessed using multiple linear regression assuming an allele dose (additive effect) on BMD (adjusted for age and sex). Statistically significant (at the unadjusted 5% level) associations were seen with 7 SNPs in 5 of the candidate genes. Two SNPs showed statistically significant association with more than one BMD site. Significant association was seen between BMD at all three sites with the VDR SNP rs731246 (L2-L4 p=0.038; neck of femur p=0.001 and total hip p<0.001). The T allele was consistently associated with lower BMD than the C allele. Significant association was also seen for the P2RX7 SNP rs3751143 where the G allele was consistently associated with lower BMD than the T allele, (L2-L4 p=0.069; neck of femur p=0.024, total hip p=0.045).